AD, Volume 37, n° 1, 2012 - Full Issue (Africa Development, 2021)
Selected papers from the 12th CODESRIA General Assembly Contents Introduction – The ‘Missing’ Concept: What is the ‘Public Sphere’ Good for? Abdul Raufu Mustapha ..................... 1 Interrogating Public Sphere and Popular Culture as Theoretical Concepts on their Value in African Studies Wendy Willems ................................... 11 The Public Sphere in 21 Century Africa: Broadening the Horizons of Democratisation Abdul Raufu Mustapha ......................... 27 Public Sphere and Epistemologies of the South Boaventura de Sousa Santos ............ 43 The Emergence of Public Spheres in Colonial Cameroon: Palm Wine Drinking Joints in Bamenda Township Nicodemus Fru Awasom .................. 69 Ambivalence and Activism: Netizens, Social Transformation and African Virtual Publics Yunusa Z. Ya’u ................................... 85 The Internet as Public Sphere: A Zimbabwean Case Study (1999-2008) Kudakwashe Manganga ................... 103